- Correlation between dental fluorosis risk and bone specific alkaline phosphatase, osteocalcin, matrix metalloproteinase and parathyroid hormone in children: Bone-specific Alkaline Phosphatase, Osteocalcin, Matrix Metalloproteinase, and Parathyroid Hormone Levels and the Risk of Dental Fluorosis - Wang, Yufeng (Journal of Medical Biochemistry, 2024)
Objective Investigating the association between dental fluorosis occurrence in children and bone metabolism-related indicators including bone-specific alkaline phosphatase (BALP), osteocalcin (OC), matrix metalloproteinase (MMP-2, MMP-9, MMP-20), and parathyroid hormone (PTH).Methods A total of 189 cases of school-age children underwent health examinations in our hospital were enrolled, according to the presence or absence of dental fluorosis, they were divided into fluorosis group (n=97) and fluoride-free group (n=92), and the serum BALP, OC, MMP-2, MMP-9, MMP-20, and PTH levels of the two groups were compared, relevant clinical data were collected.In this study, multivariate logistic regression was employed to examine the factors associated with the development of dental fluorosis in children. Results The urine fluoride levels, BALP, MMP-2, and MMP-9 of the children influorosis group were higher thanfluoride-free group, and the mother’s educational level, per capita annual household income, OC, and PTH were lower thanfluoride-free group (P<0.05).Based on Spearman correlation analysis, a positive correlation was identified between the urinary fluoride level, the extent of dental fluorosis, and indicators such as BALP, MMP-2, and MMP-9. (r=0.618, 0.558, 0.567, 0.597, 0.602, 0.571, P<0.001), and negatively correlated with OC and PTH (r=-0.580, -0.603, -0.549, -0.515, P<0.001).As the urinary fluoride level and the extent of dental fluorosis increased, there was a gradual elevation in serum BALP, MMP-2, and MMP-9 levels in children, while OC and PTH levels gradually decreased (P<0.05).After adjusting for confounding factors including urinary fluoride,maternal education level, and per capita annual household income, multivariate Logistic regression analysis showed that BALP, OC, MMP-2, MMP-9, PTH were independently associated with the risk of dental fluorosis (P<0.05). Conclusion High BALP, MMP-2, MMP-9, low OC, and PTH are independent factors affecting the occurrence of dental fluorosis and are related tothe extent of dental fluorosis.